ANALISIS PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH RIGHT ISSUE PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2021 - Muhammad Fauzi; Noviarti; Arifin Siagian (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
The purpose of this study is to determine whether there are differences in financial performance before and after the rights issue on the variables Current ratio, Total assets Turnover, Debt to Equity Ratio and Net Profit Margin in retail companies listed on the Indonesia Stock Exchange for the period 2013-2021. The sample selection method used purposive sampling. The population in this study were 7 retail companies listed on the Indonesia Stock Exchange for the period 2013-2021. The data analysis method used in this study used descriptive statistical analysis, normality test and different test. The results of the study using the paired sample T-test showed that the current ratio variable was 0.175, the total assets turnover was 0.199, the debt to equity ratio was 0.421 and the net profit margin was 0.168 indicating that the significance level for the observed data was higher than the significance level (0.05). Overall, there is no difference between these results before and after the rights issue for retail companies listed on the Indonesia Stock Exchange for the period 2013-2021.